Abordagem biográfica: um caminho para refletir em serviço a formação inicial do professor de inglês na UEMS de Cassilândia - Garcia, Telma de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
This research presents the belief that a teachers development occurs over the course of his or her life. It is necessary to remember the importance of the curriculum at each school level, in this case, the graduate level. I intend to relate the experience of a Inicial Model of Reflective that occured in the Letters Course in Teaching English Pratical Subject at Universidade Estadual de Mato Grosso do Sul (UEMS) which is located in Cassilândia city. Results of this study of the reflective model teaching in the English Practical subject included changes in the graduate Letters Course curriculum. As the professor of this subject, I undertook this research to discover with the help of Biography Approach these result of these changes as they are seen today in those former students in the English language who are now in service. The result will assist comprehension of the initial research, and establish a closer relationship between the curriculum as seen by the students while in graduate studies and the teaching environment which they will encounter after the graduates enter service.

Esta pesquisa apresenta a crença de que a formação do professor se faz no decorrer da sua trajetória de vida, no entanto, convém lembrar a importância de cada nível escolar, neste caso, a graduação. A partir de uma proposta de Modelo de Formação Inicial de Ensino Reflexivo na disciplina Prática de Ensino da língua inglesa que permitiu mudanças no currículo do Curso de Letras da UEMS de Cassilândia no período da graduação, no papel de professora da disciplina, busco através da Abordagem Biográfica averiguar como esta proposta se manifesta atualmente nestes alunos graduados em língua inglesa que estão em serviço, para que o resultado da proposta do Modelo de Formação Inicial de Ensino Reflexivo seja melhor compreendida, a fim de estabelecer um vínculo mais próximo entre teoria e prática no pré-serviço e em serviço.
Keywords: Educação; Universidade Estadual do Mato Grosso do Sul; Língua inglesa - Formação de professores; Cassilândia (MS)